New Uzbekistan: Administrative Management Reform - Chuboeva Ozodakhon (Zien Journals, 2022)
This article describes the process of modernization of the country in recent years, the adopted normative documents on the transition of the administrative system of New Uzbekistan to a new process, radical reforms in public administration and administrative mechanisms. Particular attention is paid to the activity of the President of the Republic of Uzbekistan Shavkat Mirziyoyev in the organization of the new administrative administration of Uzbekistan.
Keywords: New Uzbekistan; reform; administration; awakening